Long-Run Determinants of Inflation in Malaysia and Indonesia: Does Geopolitical risk matter? - Yahya, Yusri; Pamuncak, Mohammad Bintang (Journal of Sustainable Economics, 2023)
This study attempts to investigate the determinants of inflation in Malaysia and Indonesia in the long run. By using macroeconomic variables that theoretically matter to manage inflation such as money supply and exchange rate, this study also includes geopolitical risk index as proxy of uncertainty to be investigated further as another determinant that may cause the increasing of inflation rate in Malaysia and Indonesia. The data covers the period 2014:M11 to 2023:M8. Autoregressive distributed lag (ARDL) approach is employed to determine the long-run relationship. The main findings in this study demonstrate that the money supply and geopolitical risk are among the determinants of inflation in Malaysia in the long run. Meanwhile contrary to that, only money supply determines inflation in Indonesia. The finding indicates that money supply and geopolitical risk matter to inflation management. Hence, this study suggests that monetary authorities must take an active role towards money supply and geopolitical risk issue.